Assessment of glomerular morphological patterns by deep learning algorithms [research data] - Weis, Cleo-Aron Thias (Universität, 2022)
Test data and models to the paper "Assessment of glomerular morphological patterns by deep learning algorithms". Different, from other groups, defi...
Gesehen am 07.02.2022
Keywords: Forschungsdaten; Datenbank